Dermatoglyphic profile and somatotype of Brazilian athletes of speed canoeing - Soares de Sousa, A. P.; Ribeiro Ferreira, H.; da Silva Novaes, J.; Fernandes Filho, J. (SportLogia, 2018)
The focus of this study was analyze dermatoglyphic profile and somatotype of Brazilian athletes of speed canoeing. This study is descriptive comparative and involved a sample of n = 60 male athletes of canoeing speed, divided into four groups according by the proof and yield classification: ka= high performance of kayak, Ki=intermediate performance of kayak, Ca=high performance of canoe and Ci=intermediate performance of canoe. For dermatoglyphic was used the protocol of Cummins and Midlo, and to somatotype protocol of Heath & Carter. Statistical analyzes were performed using Kruskal-Wallis test and Bonferroni test. Regarding the dermatoglyphic sample showed a predominance of "L" and the digital formula "L > W", featuring athletes of speed and strength, power and coordination as well as is necessary in canoeing. No significant differences in D10, SQTL, MESQTL and MDSQTL between groups. The mean of somatotype was the mesomorph, featuring athletes with extremely strong structure and low levels of body fat. It showed statistically significant differences between the groups when it came somatotype index. Studies such as this aims to optimize strategies for selection and guidance training of Brazilian elite athletes.